PERCEPTIONS OF TUBAN UMKM PREPETATORS ABOUT MICRO PPKM NEWS IN ONLINE MEDIA - Ananda Araaf Putro; Ririn Puspita Tutiasari (Universitas Islam Balitar, 2021)
The Micro PPKM policy is often a polemic in the community in the current pandemic conditions. This is related to the public perception that PPKM Micro is a very detrimental policy, but there are also people who agree with the Micro PPKM policy. This perception is inseparable from the news that appears in the media, one of which is online media that is often accessed in this millennial era. Therefore, the researcher wanted to know the perception of Tuban UMKM prepetators about micro PPKM news in Online Media. The choice of Tuban City as the research location was because Tuban had become the highest Covid case in East Java and there had also been a violation of the Micro PPKM by UMKM prepetators in Tuban. In this study, the method used is descriptive qualitative with data collection techniques using in-depth interviews. For the theory, the researcher uses the new media theory because it is in accordance with the object of research that is reported through online media. The results obtained from this researcher are that UMKM prepetators have a positive perception of PPKM Micro coverage in online media.